2019
DOI: 10.1021/acs.molpharmaceut.9b00772
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Complexation into a Coamorphous System Dramatically Enhances Dissolution and Eliminates Gelation of Amorphous Lurasidone Hydrochloride

Abstract: As a BCS II drug, the atypical antipsychotic agent lurasidone hydrochloride (LH) has low oral bioavailability mainly because of its poor aqueous solubility/dissolution. Unexpectedly, amorphous LH exhibited a much lower dissolution than that of its stable crystalline form arising from its gelation during the dissolution process. In the current study, a supramolecular coamorphous system of LH with l-cysteine hydrochloride (CYS) was prepared and characterized by powder X-ray diffraction and differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 78 publications
1
21
0
1
Order By: Relevance
“…Meanwhile, it was found that pHCA showed some shifts for −OH (836 → 840 cm –1 ), −COOH (862 → 859 cm –1 ), CC (1635 → 1628 cm –1 ), and aromatic ring (1605 → 1603 cm –1 ). In comparison to the reported amorphous LH, it can be found that the Raman spectra of coamorphous LH–CA/pHCA (1:1) had shifted remarkably. These obvious shifts indicate that the coamorphous LH and CA/pHCA (1:1) systems might be formed via intermolecular hydrogen bonds.…”
Section: Resultsmentioning
confidence: 55%
“…Meanwhile, it was found that pHCA showed some shifts for −OH (836 → 840 cm –1 ), −COOH (862 → 859 cm –1 ), CC (1635 → 1628 cm –1 ), and aromatic ring (1605 → 1603 cm –1 ). In comparison to the reported amorphous LH, it can be found that the Raman spectra of coamorphous LH–CA/pHCA (1:1) had shifted remarkably. These obvious shifts indicate that the coamorphous LH and CA/pHCA (1:1) systems might be formed via intermolecular hydrogen bonds.…”
Section: Resultsmentioning
confidence: 55%
“…Compared with the spectra of EGC and 5-HMF, the absorption peak positions of the complexes in these wavenumber changed greatly, and the intensity of the absorption peak becomes weaker. This may be the transformation from crystalline to amorphous form, with the disruption of lattice causing a change in molecular conformation [37]. In addition, no new chemical bonds and functional groups were observed in the FRIR spectra of the complexes.…”
Section: Ftir Results Analysismentioning
confidence: 95%
“…Teknologi Spektroskopi Raman hampir sama dengan Infra Red, perbedaannya yaitu pada Spektroskopi IR bergantung pada perubahan momen dipol, sensitif terhadap ikatan polar (seperti OH, N-H dan C=O), sedangkan Spektroskopi Raman, bergantung pada perubahan polarisasi molekul, sensitif terhadap ikatan non polar (seperti C-C, C-S, dan C=C). Oleh karena itu, dimungkinkan untuk memperoleh informasi struktur komplementer molekul dengan kombinasi spektroskopi IR dan Raman [69].…”
Section: Spektroskopi Ramanunclassified